2021
DOI: 10.1371/journal.pone.0246366
|View full text |Cite
|
Sign up to set email alerts
|

Development of a coronavirus disease 2019 nonhuman primate model using airborne exposure

Abstract: Airborne transmission is predicted to be a prevalent route of human exposure with SARS-CoV-2. Aside from African green monkeys, nonhuman primate models that replicate airborne transmission of SARS-CoV-2 have not been investigated. A comparative evaluation of COVID-19 in African green monkeys, rhesus macaques, and cynomolgus macaques following airborne exposure to SARS-CoV-2 was performed to determine critical disease parameters associated with disease progression, and establish correlations between primate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 33 publications
12
80
3
Order By: Relevance
“…To date, only a few studies have examined disease presentation following inhalation of aerosolized SARS-CoV-2, despite the potential relevance of this route of exposure [22][23][24][25][26]. Furthermore, these studies only examined disease presentation following exposure to a single dose of SARS-CoV-2.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few studies have examined disease presentation following inhalation of aerosolized SARS-CoV-2, despite the potential relevance of this route of exposure [22][23][24][25][26]. Furthermore, these studies only examined disease presentation following exposure to a single dose of SARS-CoV-2.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Such particles are potentially hazardous as they would remain airborne for extended periods of time, and multiple studies have demonstrated that SARS-CoV-2 present in aerosol particles in this size range can remain infectious for long durations under some conditions [16][17][18][19][20][21]. Finally, it has been shown that nonhuman primates exposed to aerosols with aerodynamic diameters less than 5 μm containing SARS-CoV-2 develop disease similar to COVID-19 in humans [22][23][24][25][26]. Taken together, these studies suggest that transmission of SARS-CoV-2 by aerosols generated from the respiratory tract may be possible.…”
Section: Introductionmentioning
confidence: 99%
“…During the entire study, including the acute infection phase, only mild clinical symptoms were noticed. This sharply contrasts with findings of others that described SARS-CoV-2-induced clinical disease, with clear signs of fever directly following infection, respiratory symptoms, and changes in hematology and clinical chemistry parameters [46, 48]. Unbiased measurement of the body temperature and activity of each animal was performed continuously by using telemetry.…”
Section: Discussionmentioning
confidence: 83%
“…The study specifically focused on the post-acute phase of the SARS-CoV-2 infection in rhesus and cynomolgus macaques, defined as the 3-4 weeks period following the disappearance of detectable virus from the nose and throat swab samples. The majority of published COVID-19 NHP studies concentrate on the first two weeks of infection when evidence was found for acute viral interstitial pneumonia and virus was cleared from the nose and throat samples and lung lavages [29, 33, 35, 46, 60]. As the PET-CTs performed in this study on days 8 and 10 pi revealed an increase in 18 F-FDG-uptake in the lungs and various tracheobronchial lymph nodes, it was decided to extend the observation period with weekly PET-CTs for all macaques for several weeks (rhesus macaques 35 or 36 days pi, for cynomolgus macaques 38 or 42 days pi, depending on the PET-CT findings).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation